Unlocking Temporal Leadership to Handle Project Team Performance under Team Conflict (International Journal of Applied Research in Management and Economics, 2021)
It is discussed in different studies that the performance of any team is directly or indirectly dependent on the leadership of that team. But there are always some circumstances which affect the performance of a team on various points. These circumstances may include team conflict and its three sub-level conflicts which include task conflicts, relationship conflicts, and process conflicts. The proposed article will be a joint venture of Information Technology and Project Management discipline in which quantitative research method is used. Given the relationship between team temporal leadership and project team performance, it is obligatory for a leader of the technical team to be well aware of managing the conflicts that arise among a team and also be well aware of resources provided by higher-ups. The research will highlight 1) the negative effect of team conflict on the performance of a team, 2) the influence of temporal leadership on team performance and 3) the role of temporal leadership to overcome negative impact of conflicts to improve project team performance.